CITRA â€œAYAHâ€ DALAM NOVEL SABTU BERSAMA - Ardiyansyah, Bagus; Nugroho, Wahyu Budi; Zuryani, Nazrina (JURNAL ILMIAH SOSIOLOGI (SOROT), 2017)
This research attempts to show parts of father’s image in the narrative or story of the novel Sabtu Bersama Bapak by Adhitya Mulya. This research uses the critical discourse analysis method from Norman Fairclough, such as text analysis, discourse practice, and social practice with analysis of patriarchal language theory from Dale Spender and patriarchal culture from Sylvia Walby. The result showed that the dominant father’s image is manifested from the use of the husband's name behind the wife's name to show the identity of his family, the language used in the conversation is arranged in such a way that it harms women, and up to regulate the survival of all members of his family even though he (father) has died. In the discourse practice, namely the production of texts, Adhitya Mulya wrote the novel Sabtu Bersama Bapak because of anxiety as a father in raising children feel there are social grips in society not in line with himself. Therefore, the point of view used in this novel is the point of view of the man and the backbone of his story, a man who gives a message to men as well. Based on this, through the consumption of the text, namely the viewpoint of the researcher himself, The story in this novel represents patriarchal ideology. The view of the image of men as the master of power and the image of women as controlled, in general, described in this novel through the position of wife and child in the dominance of patriarchal ideology. Keywords: Critical discourse analysis, language and culture of patriarchy, father’s image.